Hubungan Pola Asuh Orang Tua terhadap Kejadian Diabetes pada Anak Usia Sekolah - Wenny Rahmawati; Ika Arum Dewi Satiti (Oksitosin : Jurnal Ilmiah Kebidanan, 2024)
Elevated blood sugar levels are a sign of a metabolic disease called Diabetes Mellitus (DM). Several factors including the environment are contributors to the incidence of DM. The role of parents is mainly related to the child's lifestyle, including diet and food intake for the child. The lifestyle fostered in the family will affect the health of children. The purpose of this study was to analysis the parenting style of parents towards early diagnosis of diabetes based on blood glucose levels in children. A cross-sectional design and descriptive correlational design were used for this study. This study involved all students at SDN 2 Kepuharjo in August 2023 involving 92 children with total sampling technique. This study used the Parental Authority Questionaire instrument, which consists of twenty question items that assess how parenting is done. Details of the characteristics of the respondents were mostly 11 years old with 47 children (51.1%) and were in grades 5 and 6. The most respondents were female with 49 children (53.3%). Working mother status was at 84 (91.3%). 53 children with less parenting (57.6%). The results of the examination of blood sugar levels obtained were 17 children (18.5%) in the high category. Conclusion There is a correlation between parenting patterns and the number of cases of diabetes in school-age children in elementary schools with a p value of 0.006.